Comparison of Safety Factor Using the Finite Element Method and The Janbu Method (Case Study: Morowali Regency) - Sangle, Pebrinar Riani; Tonapa, Suryanti Rapang; Pakalla, Larawati (Rekayasa Sipil, 2026)
Slope stability is a problem often encountered in construction activities, including mining and civil engineering. Slope stability analysis can be performed using various methods, such as the limit equilibrium method (LEM) and the finite element method (FEM). The objective of this study is to analyze slope stability in Morowali Regency. The method used is finite element analysis using Plaxis software version 8.2.  Furthermore, the analysis is conducted using the limit equilibrium method (LEM), which is the Janbu method. The results of the study show that the safety factor (SF) obtained from the analysis using Plaxis version 8.2 was 1.219, while that based on the Janbu method was 1.376. The differences in results show that the two methods use different approaches in calculating slope stability. The Janbu method evaluates slope stability based on force equilibrium, assuming a specific landslide plane, and does not consider stress-strain development. In contrast, FEM uses the Strength Reduction Method, which can more realistically represent stress redistribution, plastic zone development, and collapse mechanisms. As a result, FEM safety factor values tend to be smaller. The results of this study indicate that the FEM method provides a more realistic failure mechanism for slope stability than the LEM method. Despite the difference in values, both methods show consistent stability trends, so it can be concluded that FEM and the Janbu Method can be used complementarily in slope stability evaluation.